A rare case of spontaneous carotid sheath abscess presenting as a painful neck mass - Ahmad Tabatabaeishoorijeh, BS; Bright Benfor, MD; Simon J. Montelongo, DO; Eric K. Peden, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Infections of the carotid arteries and sheath without any underlying etiology are extremely uncommon. In this article, we report the successful open repair of a right carotid sheath abscess in a 71-year-old woman with multiple comorbidities. The repair consisted of excision of the affected carotid segment and reconstruction by interposition of a reversed great saphenous vein graft. Postoperative Doppler ultrasound examination showed patent right carotid artery, and the patient demonstrated no recurrence postoperatively. This case suggests that, although rare, spontaneous carotid sheath remains a possible cause of neck mass, warranting high suspicion index for optimal treatment in a timely manner to avoid further complications.